Effects of Increasing Balance Task Difficulty on Postural Sway and Muscle Activity in Healthy Adolescents - Gebel, Arnd; Lüder, Benjamin; Granacher, Urs (Frontiers in Physiology, 2019)
Evidence-based prescriptions for balance training in youth have recently been established. However, there is currently no standardized means available to assess and quantify balance task difficulty (BTD). Therefore, the objectives of this study were to examine the effects of graded BTD on postural sway, lower limb muscle activity and coactivation in adolescents. Thirteen healthy high-school stu-dents aged 16 to 17 volunteered to participate in this cross-sectional study. Testing involved partici-pants to stand on a commercially available balance board with an adjustable pivot that allowed six levels of increasing task difficulty. Postural sway (i.e., total center of pressure [CoP] displacements) and lower limb muscle activity were recorded simultaneously during each trial. Surface electromyog-raphy (EMG) was applied in muscles encompassing the ankle (m. tibialis anterior, medial gas-trocnemius, peroneus longus) and knee joint (m. vastus medialis, biceps femoris). The coactivation index (CAI) was calculated for ankle and thigh muscles. Repeated measures analyses of variance revealed a significant main effect of BTD with increasing task difficulty for postural sway (p<0.001; d=6.36), muscle activity (p<0.001; 2.54<d<2.93), and CAI (p<0.001; 1.32<d<1.41). Multiple regres-sion analyses showed that m. tibialis anterior activity best explained overall CoP displacements with 32.5% explained variance (p<0.001). The observed increases in postural sway, lower limb muscle activity, and coactivation indicate increasing postural demands while standing on the balance board. Thus, the examined board can be implemented in balance training to progressively increase BTD in healthy adolescents.